2020
DOI: 10.3390/diagnostics10110879
|View full text |Cite
|
Sign up to set email alerts
|

The Dwindling Microbiota of Aerobic Vaginitis, an Inflammatory State Enriched in Pathobionts with Limited TLR Stimulation

Abstract: While bacterial vaginosis (BV) is a well-known type of vaginal dysbiosis, aerobic vaginitis (AV) is an inflammatory condition that remains understudied and under-recognised. It predisposes women to serious complications including urogenital infections and pregnancy problems. Here, we investigated the bacterial community in AV to explore its possible role in AV pathogenesis. We collected vaginal lavage fluid samples of women (n = 58) classified by wet-mount microscopy as suffering from AV or BV and included an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…A recent study showed that increased numbers of Prevotella bivia and P. disiens could help to predict CIN2+ in HR-HPV-positive women [ 44 ]. Interestingly, recently P. bivia was also found to be one of the most important representatives in the microbiome of AV, alongside Streptococcus agalactiae [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that increased numbers of Prevotella bivia and P. disiens could help to predict CIN2+ in HR-HPV-positive women [ 44 ]. Interestingly, recently P. bivia was also found to be one of the most important representatives in the microbiome of AV, alongside Streptococcus agalactiae [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…NGS provides a relative abundance measure, which may underestimate the presence of some bacterial species, due to e.g., high total concentrations of other bacterial species. For example, L. iners has a 15-fold higher concentration than L. crispatus by qPCR [ 29 ], and another study using genus specific primers did not observe statistical difference in the total number of lactobacilli comparing normal vaginal microbiota to BV [ 56 ]. This could result in a microbiota, which by NGS would have a relative abundance skewed by a high total abundance of e.g., L. iners which may “cover-up” VD bacteria such as Gardnerella spp.…”
Section: Discussionmentioning
confidence: 99%
“…may be underestimated by relative 16S rRNA gene sequencing [ 53 ]. Typically, BV has a significantly higher total bacterial load compared to normal vaginal microbiota [ 56 ]. For this reason, it is important to acknowledge that underestimated bacteria by relative abundances may still have a physiological effect.…”
Section: Discussionmentioning
confidence: 99%
“…DIV/AV: The diagnosis of DIV/AV should be based on a combination of clinical features and microscopic findings ( Oerlemans et al., 2020 ). The clinical features are as follows: vulvar erythema; vulvar swelling; thinning of the vaginal mucosa; vaginal congestion; scattered bleeding points; and yellow-colored vaginal secretion, increased discharge or pruritus.…”
Section: Diagnosis Of Mixed Vaginitismentioning
confidence: 99%